2008
DOI: 10.1002/hrm.20210
|View full text |Cite
|
Sign up to set email alerts
|

Supporting a diverse workforce: What type of support is most meaningful for lesbian and gay employees?

Abstract: We examine differences in type of support (i.e., supervisor, coworker, organizational) received by lesbian, gay, and bisexual (LGB) employees and the relationship between type of support and relevant outcomes (job and life satisfaction, outness of sexual orientation). Surveys were administered to 99 LGB individuals, and results indicate that support is best viewed as a multi‐dimensional construct composed of supervisor, coworker, and organizational support for LGB employees. Overall, supervisor support was rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
185
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(220 citation statements)
references
References 56 publications
(89 reference statements)
12
185
1
8
Order By: Relevance
“…Those who were out also had lower conflict between work and home, lower role ambiguity, and lower role conflict (Day & Schoenrade, 1997). Decisions about disclosure are related to perceptions of the climate for GLBT employees, including perceived managerial and peer attitudes and organizational policies (Griffith & Hebl, 2002;Huffman, Watrous-Rodriguez, & King, 2008;Ragins, 2008).…”
Section: Sexual Orientation As An (Invisible) Aspect Of Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Those who were out also had lower conflict between work and home, lower role ambiguity, and lower role conflict (Day & Schoenrade, 1997). Decisions about disclosure are related to perceptions of the climate for GLBT employees, including perceived managerial and peer attitudes and organizational policies (Griffith & Hebl, 2002;Huffman, Watrous-Rodriguez, & King, 2008;Ragins, 2008).…”
Section: Sexual Orientation As An (Invisible) Aspect Of Diversitymentioning
confidence: 99%
“…All workers should be educated on the organization's stance regarding diversity and inclusion-and that it includes sexual orientation-regardless of whether or not there is protective legislation in a particular locale. Huffman et al (2008) recommended that diversity training include support-based training, emphasizing how to be a fair and supportive colleague or supervisor to GLBT employees.…”
Section: Insert Table 2 About Herementioning
confidence: 99%
“…Embora grande parte das pesquisas (HUFFMAN; WATROUS-RODRIGUEZ; KING, 2008;LUCAS;KAPLAN, 1994;TRAU, 2015) sugira que um clima organizacional que favorece a afirmação da identidade sexual promove resultados positivos para o empregado, o coming out nem sempre é visto como a melhor opção do empregado. Isso porque o preconceito e atitudes homofóbicas ainda se fazem muito presentes nas organizações (BICALHO; DINIZ, 2009;CAPRONI et al, 2014;GARCIA;SOUZA, 2010;IRIGARAY et al, 2010).…”
Section: Razões E Efeitos Do Coming Outunclassified
“…Um ambiente organizacional acolhedor incentiva a revelação da identidade sexual, fazendo com que o desenvolvimento de atitudes organizacionais positivas relacionadas à satisfação no trabalho e comprometimento organizacional possa ocorrer (HUFFMAN et al, 2008;TRAU, 2015).…”
Section: Razões E Efeitos Do Coming Outunclassified
“…This is due to directive 2000/78/EC of the European Council, and makes antidiscrimination guidelines on sexual orientation largely irrelevant for European diversity management practice, as they are, in any case, obligatory, at least in terms of regulating everyday interaction between employees or between employees and supervisors. More generally, it was shown that the feeling of being supported by the employing organization in issues that are related to homosexuality in the workplace (Griffith and Hebl 2002), and especially the experienced support of direct supervisors (Huffman et al 2008), positively affects individuals' job satisfaction. The perception of general compatibility between employee and organization seems to be more relevant for homosexual employees than for heterosexuals (Lyons et al 2005).…”
Section: Sexual Orientation Diversity Managementmentioning
confidence: 99%